Project-Based Learning Model with Hybrid Learning in EFL Critical Reading: Need Analysis - Ismail, Hijril; Hatmanto, Endro Dwi; Tusino, Tusino; Ramdhani, M. Maarif (Indonesian Research Journal in Education |IRJE|, 2024)
analyze, evaluate, and reflect on information critically and objectively. The research aims to identify and describe the students’ needs for a project-based learning model through hybrid learning in EFL critical reading. This study was conducted as survey research within the English Education Study Program at Muhammadiyah University of Mataram, Muhammadiyah University of Purworejo, and Education University of Yogyakarta. The questionnaire used for data collection comprised 63 statements across 11 factors. The research result indicates that all of the students expressed a need for these eleven factors; learning objectives, topic needs, teaching material requirements, assessment needs, the need for PJBL syntax, need for hybrid learning, social system needs, requirement principle of reaction, need of support system, learning impact needs, and need for impact accompanying learning. We recommended further studies to implement these factors in teaching critical reading in English foreign language.